Human and Civil Rights in Israel - R. L. Iliev (Московский журнал международного права, 2009)
The article deals with basic principles, features and specific character of the development of human and citizen rights in Israel. Constitutional and legal consolidation of major part of these rights was achieved in the course of “Constitutional revolution”. The religious law which dominates in regulating private status (marriage and divorce) preserves significant influence in the country. In the absence of a written constitution the main guarantor of human and citizen rights is the High Court. The established status of a person in the State of Israel lets consider the country as a lawful democratic state.